Collateral Damage: The Predicament of History and Memory in the Traumatic Event - Epafras, Leonard C. (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2009)
This article is an attempt to revisit the problem of history and memory in the construction of Indonesian violent past, notably the 1965 putsch and its aftermath. The engagement is based on the understanding that history , as a product of scientific discipline, is mainly seeing the past prospectively, while the memory of people, particularly those who are affected by the traumatic event, is seeing it retrospectively. In these two tendencies, generally the standard account champions the historian version, by sacrificing the ordinary people’s account. Contrary to this, by taking Bakhtinian dialogical reading of history, the article gives an ample space to the many-voicedness of historical account , to the complexity of historical struggle, and to seeing the dynamic of the past beyond the stereotypes of “victim” vs.”perpetrator”